EKSPLORASI Bacillus spp. PADA BEBERAPA RHIZOSFER GULMA DAN POTENSINYA SEBAGAI AGENS PENGENDALI HAYATI PATOGEN TANAMAN SECARA IN VITRO - Rana Virga Tesha Syofiana; Rachmi Masnilah (Universitas Trilogi, 2019)
One group of rhizobacteria that has been widely studied as a biological controlling agent is Bacillus spp. Through the mechanism of induction of resistance and antibiosis, these bacteria are able to suppress the growth of plant pathogens. Its ability to quickly colonize plant roots and broad adaptability to the environment causes Bacillus to spread in nature, especially in the rhizosphere. This study aims to determine the presence of Bacillus in several rhizosphere weeds and their ability to inhibit plant pathogen growth in vitro. This study consisted of two stages, namely, (1) sampling activities carried out in the Kalisat area, Jember Regency, and (2) isolation, selection and identification. Based on the results of the study, 17 Bacillus spp. Isolates. which was successfully isolated from several rhizosphere weeds. The results of Bacillus spp. in vitro the inhibition was obtained by 73% in suppressing Fusarium sp. and 14 mm clear zone formed by Bacillus against X. oryzae pv. oryzae. 5 superior Bacillus isolates obtained from the antagonist test were identified as B. subtilis, B. licheniformis, B. alvei, and B. coagulans.Keyword: Bacillus spp., biological agents, weeds of rhizosphere